2017
DOI: 10.1083/jcb.201704102
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-cadherin provides tolerance to centrosome amplification in epithelial cancer cells

Abstract: Centrosome clustering is essential for the survival of cells containing supernumerary centrosomes. Rhys et al. show that centrosome clustering is a two-step mechanism in which increased cortical contractility, driven by loss of E-cadherin, restricts centrosome movement, facilitating HSET-mediated clustering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 56 publications
15
95
0
Order By: Relevance
“…Besides stochastic effects, other aspects of the spindle mechanics will have to be considered to make the model less simplistic. Those include influence of merotelic errors of assembly on the force balance (25), space-dependent motor regulation (15), viscoelastic properties of the spindle (23), and role of the cortex flow in bringing CSs together (73), not to mention biophysical details of the magnitudes and spatial dependencies of the forces in the spindle that remain under-researched (22,47,74).…”
Section: Discussionmentioning
confidence: 99%
“…Besides stochastic effects, other aspects of the spindle mechanics will have to be considered to make the model less simplistic. Those include influence of merotelic errors of assembly on the force balance (25), space-dependent motor regulation (15), viscoelastic properties of the spindle (23), and role of the cortex flow in bringing CSs together (73), not to mention biophysical details of the magnitudes and spatial dependencies of the forces in the spindle that remain under-researched (22,47,74).…”
Section: Discussionmentioning
confidence: 99%
“…Centrosome aberrations are also prominent in cancers, including pre‐invasive in situ carcinomas (Lingle et al , ; Pihan et al , ; Guo et al , ), suggesting that they contribute actively to carcinogenesis (Lingle et al , ; Nigg, ; Pujana et al , ; Zyss & Gergely, ; Godinho & Pellman, ; Gonczy, ). Interestingly, cancer cells adapt to centrosome aberrations in multiple ways, notably through clustering of supernumerary centrosomes (Nigg, ; Quintyne et al , ; Rhys et al , ). Best documented is the influence of centrosome aberrations on chromosomal instability, a hallmark of cancer (Ganem et al , ; Silkworth et al , ), and increasing evidence also suggests an impact on tissue architecture (Nigg, ; Godinho & Pellman, ; Kazazian et al , ; Raff & Basto, ).…”
Section: Introductionmentioning
confidence: 99%
“…Extra centrosomes can be generated in diploid NBs by Plk4/Sak over-expression (OE) [7]. In SakOE NBs as in other cells containing extra centrosomes, the minus-end directed kinesin Ncd (Drosophila ortholog of HSET) plays an essential role in promoting centrosome clustering [18,31]. We tested whether Ncd was also contributing to the initial clustering observed in polyploid NBs.…”
Section: Ncd/hset Is Required But Is Not Sufficient To Fully Clustermentioning
confidence: 99%
“…We tested whether DNA could function as a physical barrier that could maintain multiple spindle poles away from each other. Indeed, it has been shown that Ncd requires a minimal distance to promote clustering through cross-linking of antiparallel MTs [31]. We first established an in-silico approach.…”
Section: Abnormal Dna Content and Shape Inhibit Spindle Pole Clusteringmentioning
confidence: 99%